2008
DOI: 10.1016/j.actamat.2008.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature specific heat of the superconductor Mo3Sb7

Abstract: The low-temperature specific heat of a superconductor Mo 3 Sb 7 with T c = 2.25 ±0.05 K has been measured in magnetic fields up to 5 T. In the normal state, the electronic specific heat coefficient γ n , and the Debye temperature Θ D are found to be 34.5(2) mJ/molK 2 and 283(5) K, respectively.The enhanced γ n value is interpreted due to a narrow Mo-4d band pinned at the Fermi level. The electronic specific heat in the superconducting state can be analyzed in terms a phenomenological two BCS-like gap model wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 30 publications
5
23
0
Order By: Relevance
“…As previously reported, Ru 3 Sn 7 and Mo 3 Sb 7 dier from one another in physical properties. Mo 3 Sb 7 was rstly determined as an ordinary BCS-type superconductor with T c = 2.1 K [2], and its superconducting state may be described by two BCS-like gaps with 2∆ 1 ≈ 4.0 k B T c and 2∆ 2 ≈ 2.5 k B T c [3]. These suggestions are being strengthened by muon spin-rotation µSR studies in the superconducting state [4].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…As previously reported, Ru 3 Sn 7 and Mo 3 Sb 7 dier from one another in physical properties. Mo 3 Sb 7 was rstly determined as an ordinary BCS-type superconductor with T c = 2.1 K [2], and its superconducting state may be described by two BCS-like gaps with 2∆ 1 ≈ 4.0 k B T c and 2∆ 2 ≈ 2.5 k B T c [3]. These suggestions are being strengthened by muon spin-rotation µSR studies in the superconducting state [4].…”
Section: Introductionmentioning
confidence: 73%
“…Several important facts emerge from dierent electronic band structure calculations for Mo 3 Sb 7 [58]. To encourage the interpretation based on two-gapped model, the electronic density of states and Fermi surface data have shown that the 4d-and spelectrons forming two bands dier from one another by the Fermi velocities, and in consequence they contribute dierently to density of state (DOS) at the Fermi level, E F [3,9]. Another interesting result is the appearance of a largest peak of DOS located at around 0.035 eV below E F , pointing to the existence of the Van Hove singularity.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] As far as the superconducting pairing mechanism is concerned, there is no agreement whether Mo 3 Sb 7 is a typical s-wave electron-phonon (BCS) superconductor or some more complex state is realized. Most of the published results [2,3,[9][10][11], including first principles calculations for the cubic phase, [11] support the conventional * email: wiendlocha@fis.agh.edu.pl…”
Section: Introductionmentioning
confidence: 85%
“…However, various values of the electronic specific heat jump at the transition point were reported, [3,9,12] ∆C/γT c = 1.04−1.56 much smaller, or close to the weakcoupling BCS value 1.43. Moreover, the specific heat in the superconducting state [9,10] and the magnetic field penetration depth [13,14] behaviors were differently analyzed, in terms of either one-or two-gap BCS models. It was also proposed, that antiferromagnetic fluctuations may be responsible for the superconductivity, due to observation of the spin density wave under pressure.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation